The call of the wild - London, Jack, 1876-1916. (New York : MacMillan, 1963)
Tale of an heroic part-St. Bernard, part shepherd dog taken from sunny California and thrown into Klondike life as a sled-dog where he becomes the strongest leader.
Keywords: Animal welfare -- Juvenile fiction; Feral dogs -- Juvenile fiction; Pet theft -- Juvenile fiction; Sled dogs -- Juvenile fiction; Dogs -- Juvenile fiction; Dogs -- Fiction; Short stories; Klondike River Valley (Yukon) -- Fiction; Alaska -- Fiction; Nature stories